2012
DOI: 10.1159/000338542
|View full text |Cite
|
Sign up to set email alerts
|

The Amino Acid-Polyamine-Organocation Superfamily

Abstract: The amino acid-polyamine-organocation (APC) superfamily has been shown to include five recognized families, four of which are specific for amino acids and their derivatives. Recent high-resolution X-ray crystallographic data have shown that four additional transporter families (BCCT, TC No. 2.A.15; SSS, 2.A.21; NSS, 2.A.22; and NCS1, 2.A.39), transporting a wide range of solutes, exhibit sufficiently similar folds to suggest a common evolutionary origin. We have used established statistical methods, based on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
96
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 91 publications
6
96
0
3
Order By: Relevance
“…Strikingly, the crystal structures revealed that CaiT adopts a fold similar to that of the LeuT-type transporters (7,10,11). This places it in the amino acid-polyamine-organocation (APC) superfamily (12), which shares a conserved architecture of two inverted repeats of five transmembrane (TM) helices each, implying common mechanistic principles. Among the APC transporters, the leucine transporter LeuT from the neurotransmitter/sodium symporter family (10), the betaine transporter BetP from the betaine/choline/ carnitine transporter family (13), the benzyl-hydantoin transporter Mhp1 of the nucleobase/cation symport 1 family, and the Na + / galactose symporter vSGLT of the solute/sodium symporter family are substrate/sodium symporters (14,15).…”
mentioning
confidence: 99%
“…Strikingly, the crystal structures revealed that CaiT adopts a fold similar to that of the LeuT-type transporters (7,10,11). This places it in the amino acid-polyamine-organocation (APC) superfamily (12), which shares a conserved architecture of two inverted repeats of five transmembrane (TM) helices each, implying common mechanistic principles. Among the APC transporters, the leucine transporter LeuT from the neurotransmitter/sodium symporter family (10), the betaine transporter BetP from the betaine/choline/ carnitine transporter family (13), the benzyl-hydantoin transporter Mhp1 of the nucleobase/cation symport 1 family, and the Na + / galactose symporter vSGLT of the solute/sodium symporter family are substrate/sodium symporters (14,15).…”
mentioning
confidence: 99%
“…However, one cannot establish independent origin based solely on a lack of sequence similarity because sequence divergence can mask the common features of homologues that arose from a common ancestry (22)(23)(24). In establishing homology, it is imperative to use rigorous statistical methods to identify family and superfamily relationships.…”
mentioning
confidence: 99%
“…The majority of these proteins belong to the ubiquitous amino acid polyamine organocation (APC) 5 superfamily, one of the largest families of secondary transporters (1,2). The APC includes members that function as solute/cation symporters and solute/solute antiporters and are found in bacteria, archeae, fungi, protists, plants and animals (1,3). Fungal APC members belong to the yeast amino acid transporter (YAT) family (4).…”
mentioning
confidence: 99%